Association between spatial working memory and Re-experiencing symptoms in PTSD. (June 2022) - Mathew, Abel S.; Lotfi, Salahadin; Bennett, Kenneth P.; Larsen, Sadie E.; Dean, Caron; Larson, Christine L.; Lee, Han-Joo
Abstract: Background and objectives: Few studies have evaluated the link between working memory (WM) and post-traumatic stress disorder (PTSD). Further, it is unknown whether this relationship is accounted for by other relevant variables including negative affect, emotional dysregulation, or general non-WM-related cognitive control deficits, which are associated with PTSD. The purpose of this study was to determine the extent to which a computerized WM task could predict PTSD symptomology incrementally beyond the contribution of other relevant variables associated with PTSD. Methods: Thirty veterans were eligible to complete emotional symptom questionnaires, a heart-rate variability measure, and computerized tasks (i.e., emotional Stroop and automated complex span tasks). A three-stage hierarchical regression was conducted with the PCL-5 total score and symptom clusters (i.e., re-experiencing, avoidance, hyperarousal, and negative cognition/mood) as the dependent variable. Results: Results revealed that only the re-experiencing symptom cluster was significantly predicted by executive, verbal, and visuospatial WM tasks, which explained an additional 29.7% of the variance over and above other relevant variables. Most notably, the visuospatial task was the only WM task that significantly explained PCL-5 re-experiencing symptoms. Limitations: This study was based on a small sample of veterans with PTSD and causality cannot be determined with this cross-sectional study. Conclusions: Overall, the results suggest that deficits in visuospatial WM are significantly associated with PTSD re-experiencing symptoms after controlling for other relevant variables. Further research should evaluate whether an intervention to improve visuospatial WM capacity can be implemented to reduce re-experiencing symptoms. Highlights: There is a lack of research on the association between working memory and PTSD. We investigated this relationship after controlling for relevant PTSD covariates. Spatial working memory significantly correlates with PTSD re-experiencing symptoms. This data can help understand the nature of working memory deficits in PTSD.